2008
DOI: 10.1203/pdr.0b013e318184d2b5
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of the T295M Mutation Causing Glut1 Deficiency: Glucose Efflux Preferentially Affected by T295M

Abstract: Glucose transporter type 1 (Glut1) deficiency syndrome (Glut1 DS, OMIM: #606777) is characterized by infantile seizures, acquired microcephaly, developmental delay, hypoglycorrhachia (CSF glucose Ͻ40 mg/dL), and decreased erythrocyte glucose uptake (56.1 Ϯ 17% of control). Previously, we reported two patients with a mild Glut1 deficiency phenotype associated with a heterozygous GLUT1 T295M mutation and normal erythrocyte glucose uptake. We assessed the pathogenicity of T295M in the Xenopus laevis oocyte expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…This study included 3 cases of GLUT-1DS with SLC2A1 missense mutations who did not exhibit the low uptake of 3-O-methyl-D-glucose by erythrocytes. Recent study demonstrated that the specific type of mutation alter GLUT confirmation and asymmetrically affects glucose flux across the cell by perturbing efflux (glucose release in CSF) than influx (uptake of glucose) [36]. A diversity of phenotypes was observed among patients with the same mutation and even within autosomal dominant family members, suggesting a complex onset pathomechanism.…”
Section: Missense Mutationmentioning
confidence: 99%
“…This study included 3 cases of GLUT-1DS with SLC2A1 missense mutations who did not exhibit the low uptake of 3-O-methyl-D-glucose by erythrocytes. Recent study demonstrated that the specific type of mutation alter GLUT confirmation and asymmetrically affects glucose flux across the cell by perturbing efflux (glucose release in CSF) than influx (uptake of glucose) [36]. A diversity of phenotypes was observed among patients with the same mutation and even within autosomal dominant family members, suggesting a complex onset pathomechanism.…”
Section: Missense Mutationmentioning
confidence: 99%
“…The mutation was found to be pathogenic using five in silico prediction software programs (Polyphen, Panther, SIFTV2, SNPs3D and Align GVGD). It is located close to a frequent mutation, Thr295Met, which specifically alters GLUT1 conformation and disrupts GLUT1 activity [7]. Oral acetazolamide was started at a daily dose of 500 mg, resulting in immediate and complete disappearance of the attacks.…”
Section: Dear Sirsmentioning
confidence: 99%
“…nonsense, frame shift, splice junctions) often result in severe disease while missense mutants sometimes have more subtle clinical phenotypes (Leen et al, 2010). Even missense mutations that do not effect transporter expression or cell surface localization can cause neurological disease (Arsov et al, 2012; Wang et al, 2008). The phenotypic variability in the clinical presentation of G1D patients suggests nuances in the regulation of GLUT1-mediated glucose transport.…”
Section: Introductionmentioning
confidence: 99%